The Impact of Return on Asset, Debt to Equity Ratio, Current Ratio and Firm Size on Price to Book Value in Service Companies in the Property and Real Estate Sub-Sector Listed on the Indonesia Stock Exchange from 2015 to 2023 - Lena Purba, Dhonna; Kosadi, Ferry (Economic Reviews Journal, 2024)
In the Property and Real Estate Sub-Sector Listed on the Indonesia Stock Exchange from 2015 to 2023, this study aims to determine how characteristics such return on asset, debt to equity ratio, current ratio, and company size effect price to book value. The methodology used in this study is quantitative and includes a descriptive and verification approach. The statistical analysis approach of verification makes use of hypothesis testing with partial and simultaneous tests (f and t tests), multiple linear regression, Pearson product moment correlation coefficient, determination coefficient, and traditional assumption testing. The 72 financial reports of companies listed on the Indonesia Stock Exchange that are part of the Property and Real Estate Sub-Sector provide the sample data. In addition to nonprobability sampling, this study used a purposive sample method. For data processing, SPSS software version 26.0 is utilized. The results of an initial investigation indicate that there is a clear correlation between return on asset and price to book value. Price to book value is not significantly impacted by the debt to equity ratio. At most, there is very little effect of institutional ownership current ratio on price to book value. Firm size has no effect on price to book value and does not have a major impact. Concurrently, the study's results show how price to book value is affected by return on asset, debt to equity ratio, current ratio, and firm size.